EDUKASI STOP BERBURU DAN MENGKONSUMSI HEWAN LIAR PADA ANAK SD KATOLIK TES, DESA NAPAN - Simarmata, Yohanes Timbun Raja Mangihut Ronael; Ratujawa, Elthon Aditya (Jurnal Media Tropika, 2024)
This article reports on community service activities aimed at raising awareness among 6th-grade students of Tes Catholic Elementary School about the negative impacts of hunting and consuming wildlife. In this activity, we carry out a series of educational programs that include counseling, interactive discussions, and the use of visual media to convey information. The material presented covered the role of wildlife in the ecosystem, the risk of extinction, and the importance of conservation. Evaluations were conducted before and after the program, demonstrating a significant improvement in students' understanding of conservation and the impact of hunting. This activity is expected to form a positive attitude and encourage students to become agents of change in their communities.